The Suitability of Intan Pariwara's English Textbook with The Learning Styles of Eighth Grade Students at Islamic-based Schools - Rahmawati, Sustania; Jati, Sigit Pramono; Ariyanto, Ariyanto (Universitas Pahlawan Tuanku Tambusai, 2025)
This article focuses on analyzing the suitability between the English textbooks for eighth grade published by Intan Pariwara and students' learning styles. Using descriptive quantitative methods through data collection techniques such as VAK (Visual, Auditory, Kinesthetic) learning style questionnaires and content analysis of the books. This study took 31 participants from grade VIII at an Islamic-based school in Surabaya. The findings show that there is an imbalance between students' learning styles and the proportion of learning styles in textbooks, because students predominantly have an Auditory learning style, while textbooks mostly facilitate Visual. However, the auditory learning style is still facilitated quite well, while Kinesthetic is the least facilitated which has the potential to widen the learning gap for students who require hands-on practice-based learning. This research highlights the balance of learning style facilitation in textbooks to better suit students' needs and emphasize the role of teachers in selecting and sorting appropriate textbooks to achieve inclusive and balanced learning.